Respuesta :

Answer:

[tex]3 {x}^{2} + 12x = 9 \\ 3 {x}^{2} + 12x + ( - 9) = 9 + ( - 9) \\ 3 {x}^{2} + 12x - 9 = 9 - 9 \\ 3 {x}^{2} + 12x - 9 = 0 \\ 3 ({x}^{2} + 4x - 3) = 0 \\ 3 ({x}^{2} + 4x - 3) \times \frac{1}{3} = 0 \times \frac{1}{3} \\ ({x}^{2} + 4x - 3)3 \times \frac{1}{3} = 0 \times \frac{1}{3} \\ ({x}^{2} + 4x - 3) \times 1 = 0 \\ {x}^{2} + 4x - 3 \ = 0 \\ {x}^{2} + 4x - 3 + 3\ = 0 + 3 \\ {x}^{2} + 4x + 0\ = 3 \\ {x}^{2} + 4x \ =3 \\ {x}^{2} + 2(2)x + 2^{2} = 3 + {2}^{2} \\ {(x + 2)}^{2} = 3 + 4 \\ (x + 2) ^{2} = 7 \\ { ({(x + 2)}^{2}) }^{ \frac{1}{2} } = 7 ^{ \frac{1}{2} } \\ x + 2 = \ \sqrt[2]{ {7}^{1} } \\ x + 2 = \sqrt[2]{7} \\ x + 2 = \sqrt{7} \\ x + 2 + ( - 2) = \sqrt{7} + ( - 2) \\ x + 2 - 2 = ( - 2) + \sqrt{7} \\ x + 0 = - 2 + \sqrt{7} \\ x = - 2 + \sqrt{7} [/tex]

at √7 the values will be + and -

that is x = -2 + (+√7)

x = -2 + √7

and

x = -2 + (-√7)

x = -2 - √7

so x = -2±√7